A cost-effectiveness analysis of antenatal influenza vaccination among HIV-infected and HIV-uninfected pregnant women in South Africa. Issue 46 (31st October 2019) - Biggerstaff, Matthew; Cohen, Cheryl; Reed, Carrie; Tempia, Stefano; McMorrow, Meredith L.; Walaza, Sibongile; Moyes, Jocelyn; Treurnicht, Florette K.; Cohen, Adam L.; Hutchinson, Paul; Stoecker, Charles; Steinberg, Joni
Abstract: Background: Pregnant women and infants are at increased risk of severe disease from influenza. Antenatal influenza vaccination is safe and can reduce the risk of illness for women and their infants. We evaluated for South Africa the health effects of antenatal influenza vaccination among pregnant women and their infants aged <6 months old and assessed its cost-effectiveness. Methods: We constructed a decision tree model to simulate the population of pregnant women and infants aged <6 months in South Africa using TreeAge Pro Suite 2015. The model evaluated the change in societal costs and outcomes associated with a vaccination campaign that prioritized HIV-infected over HIV-uninfected pregnant women compared with no vaccination. We also examined the impacts of a campaign without prioritization. Upper and lower 90% uncertainty intervals (90% UI) were generated using probabilistic sensitivity analysis on 10000 Monte Carlo simulations. The cost-effectiveness threshold was set to the 2015 per capita gross domestic product of South Africa, US$5724. Results: Antenatal vaccination with prioritization averted 9070 (90% UI: 7407–11217) total cases of influenza among pregnant women and infants, including 411 (90% UI: 305–546) hospitalizations and 30 (90% UI: 22–40) deaths. This corresponds to an averted fraction of 13.5% (90% UI: 9.0–20.5%). Vaccinating without prioritization averted 7801 (90% UI: 6465–9527) cases of influenza, including 335 (90% UI: 254–440) hospitalizations and 24 (90% UI: 18–31) deaths. This corresponds to an averted fraction of 11.6% (90% UI: 7.8–17.4%). Vaccinating the cohort of pregnant women with prioritization had societal cost of $4689 (90% UI: $3128–$7294) per Quality Adjusted Life Year (QALY) gained while vaccinating without prioritization had a cost of $5924 (90% UI: $3992–$9056) per QALY. Conclusions: Antenatal influenza vaccination campaigns in South Africa would reduce the impact of influenza and could be cost-effective.